2018
DOI: 10.1097/md.0000000000012008
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting EEG-global-coherence with auditory and visual noise

Abstract: The present investigation documents the electrophysiological occurrence of multisensory internal stochastic resonance (MISR) in the human electroencephalographic (EEG) coherence elicited by auditory and visual noise.We define MISR of EEG coherence as the phenomenon for which an intermediate level of input noise of a sensory modality enhances EEG coherence in response to another noisy sensory modality. Here, EEG coherence is computed by the global weighted coherence (GWC), modulated by quasi-Brownian noise. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…We conclude that the global coherence in EEG signals can be augmented not only by multisensory integration of noise sources as previously reported (Mendez-Balbuena et al 2018) but also by binaural or monaural noise sources via the internal SR phenomenon.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We conclude that the global coherence in EEG signals can be augmented not only by multisensory integration of noise sources as previously reported (Mendez-Balbuena et al 2018) but also by binaural or monaural noise sources via the internal SR phenomenon.…”
Section: Discussionsupporting
confidence: 84%
“…Internal SR in the brain is a phenomenon in which the coherence between two neural signals is enhanced by the application of an intermediate level of sensory noise. Recently, Mendez-Balbuena et al (2018) showed that the application of an intermediate level of auditory noise during the sensory perception of visual noise produces an augmented response in the Global Weighted Coherence (GWC) in EEG signals. This finding suggests the presence of internal SR due to multisensory interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sensory evidence itself might be corrupted by varying amounts of noise. Interestingly, in a phenomenon referred to as cross-modal stochastic resonance, it has been found that intermediate levels of noise in one sensory modality can enhance (rather than impair) responses to weak stimuli in another sensory modality (Manjarrez et al, 2007; Mendez-Balbuena et al, 2018). Future studies should address how learned priors and sensory context interact with bottom-up sensory evidence in the brain.…”
Section: Future Directionsmentioning
confidence: 99%
“…Emerging evidence suggests that high internal neuronal noise and poor external noise filtering impact auditory perception in individuals with ASD (Park et al, 2017). Recent research has implemented new measurement methods using EEG global coherence to examine the relationship between internal neuronal noise and the application of external auditory quasi-Brownian noise vs. absence of external noise (Mendez-Balbuena et al, 2018). Few studies have examined the relationship between EDA and EEG.…”
Section: Discussionmentioning
confidence: 99%